Effectiveness and safety of the combination of sodium–glucose transport protein 2 inhibitors and glucagon-like peptide-1 receptor agonists in patients with type 2 diabetes mellitus: a systematic review and meta-analysis of observational studies - Aftab Ahmad; Hani Sabbour (Cardiovascular Diabetology, 2024)
Abstract Background Randomized controlled trials and real-world studies suggest that combination therapy with sodium–glucose transport protein 2 inhibitors (SGLT2is) and glucagon-like peptide-1 receptor agonists (GLP-1RAs) is associated with improvement in fasting plasma glucose (FPG), glycated hemoglobin (HbA1c), systolic blood pressure (SBP), body mass index (BMI), and total cholesterol levels. However, a systematic review of available real-world evidence may facilitate clinical decision-making in the real-world scenario. This meta-analysis assessed the safety and effectiveness of combinations of SGLT2is + GLP-1RAs with a focus on their cardioprotective effects along with glucose-lowering ability in patients with type 2 diabetes mellitus (T2DM) in a real-world setting. Methods Electronic searches were performed in the PubMed/MEDLINE, PROQuest, Scopus, CINAHL, and Google Scholar databases. Qualitative analyses and meta-analyses were performed using the Joanna Briggs Institute SUMARI software package and Review Manager v5.4, respectively. Results The initial database search yielded 1445 articles; of these, 13 were included in this study. The analyses indicated that SGLT2is + GLP-1RAs combinations were associated with significantly lower all-cause mortality when compared with individual therapies (odds ratio [95% confidence interval [CI] 0.49 [0.41, 0.60]; p < 0.00001). Significant reductions in BMI (− 1.71 [− 2.74, − 0.67]; p = 0.001), SBP (− 6.35 [− 10.17, − 2.53]; p = 0.001), HbA1c levels (− 1.48 [− 1.75, − 1.21]; p < 0.00001), and FPG (− 2.27 [− 2.78, − 1.76]; p < 0.00001) were associated with the simultaneous administration of the combination. Changes in total cholesterol levels and differences between simultaneous and sequential combination therapies for this outcome were not significant. Conclusion This systematic review and meta-analysis based on real-world data suggests that the combination of SGLT2is + GLP-1RAs is associated with lower all-cause mortality and favorable improvements in cardiovascular, renal, and glycemic measurements. The findings drive a call-to–action to incorporate this combination early and simultaneously in managing T2DM patients and achieve potential cardiovascular benefits and renal protection. Graphical Abstract